O conceito de forma como belo em H. C. de Lima Vaz - Xavier, Marivelto Leite (Universidade do Vale do Rio do Sinos, 2008)
This research aims to legitimize the concept os shape as beautiful in Lima Vaz. Philosophical principle of legitimacy that escapes the shape of beautiful, and is precisely why, because it was the size of eternity we can talk about the beautiful shape in Lima Vaz. Shape is to be. Or better, Shape as to be is “ens”. Therefore, being in the world as shape it´s receiving such a condition of being (Esse). There´s, thus a shape of ontological humility in receiving and a generosity in giving to be. We say that shape is not to be, but rather, “habens esse”, is the carrier exist. While there are carriers of to be or Esse, the shapes are separates substances. Consist of matters that individually and shapes, is what provides the substance is what it´s. Henceforth, the substance – “somethings that to be” – is an infinit sensitive, sensitive not only of the senses, but prior to that in a “concrete ontological unity” with this. Sensitive realize is that unit´s be concret. . Sayng the “man exist” is considering this singu
Keywords: forma; ontologia; pessoa; prudêntia; existir; ontology; person; prudentia; shape; to be; Ciências Humanas